Character Education Values in the Legend of "Mount Lewotobi" in East Flores, East Nusa Tenggara, Indonesia - Banggor, Yulianus Erson; Simanjuntak, Nensy Megawati; Purnamasari, Hetty (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
This study examines the integration of character education values in the Indonesian legend Mount Lewotobi from East Flores, East Nusa Tenggara. Character education is a fundamental aspect of human development, shaping morals and personalities to create more humane individuals, and local legends serve as valuable mediums for imparting ethical lessons. Employing a qualitative approach, this research utilized documentation as the primary data collection technique and applied Spradley’s cultural theme analysis model to analyze the narrative. Data validation was ensured through triangulation techniques. The findings reveal that the Mount Lewotobi legend conveys significant character education values, particularly in teaching ethics and manners. The study underscores the rich correlation between education and literature, emphasizing the potential of local wisdom as an effective medium for character education. By incorporating such narratives into educational curricula, students can connect with their cultural heritage while fostering moral and ethical growth, making local legends a vital resource for holistic education.